A new species of Atopophlebia Flowers (Ephemeroptera: Leptophlebiidae) from western Ecuador with ecological and biogeographic notes on the genus - Flowers, R. Wills (Zootaxa, 2012)
Atopophlebia pitculya is described from adults and nymphs from western Ecuador. Nymphs were found in leaf packs in small streams that can be intermittent in the dry season. This species along with Atopophlebia fortunensis are found associated with the accreted terranes of Central America, the Western Andes of Colombia, and the coastal mountains in northwestern Ecuador.